Snow-bed communities with dominant Salix herbacea in the Julian Alps - Martinčič, Andrej; Wraber, Tone; Dakskobler, Igor (Hacquetia, 2019)
In the alpine belt of the Julian Alps (glacial cirque Na Jezerih under Mt. Veliki Rokav, Jarečica, the Mangart Saddle and Prodi under Mt. Mangart as well as Mt. Plešivec in the rock wall of Loška Stena) we studied the phytosociology and ecology of snow-bed vegetation with dominating flowering plants Salix herbaceae, Luzula alpinopilosa, Omalotheca supina, Soldanella pusilla and Salix retusa, and numerous moss species. Based on the comparison with similar snow-bed communities in the Central, Eastern and Southern Alps we described a new association Salicetum retuso-herbaceae and classified it into the alliance Salicion herbaceae and class Salicietea herbaceae. We determined several successional stages of snow-bed vegetation on mixed calcareous-silicate bedrock that we treat as variants, in two relevés also the initial association Polytrichetum sexangularis.